Temperature Monitoring System For Infant Incubator Using Arduino - Ab Hadi, Nik Azran; Che Hasan, Mohd Hanif; Hashim, Nik Mohd Zarifie; N. R. Mohamad; A. S. Rahimi; Mohd Annuar, Khalil Azha (IJARET, 2015)
Suitable temperature is a vital element of the human being and even for machines in the industry. This study was aimed to explore the implementation of radio frequency in the certain field. For this project, the radio frequency was implemented in the NICU for the incubator system. The concept of incubator has been identified and the function of the main component has been analyzed. The use of Arduino UNO and Arduino Pro Mini was in order to provide the portable RF monitoring device along with the enhancement of the use of wireless sensor network technology. As to control and stabilize the temperature inside operation theatre, LM 35 is been placed inside the operation theatre that will perform as temperature sensor. It gives a signal to PIC16F876A to trigger the blower or heater. The temperature needs to be maintained around 18° degree to 22° degree. A prototype of radio frequency monitoring device was designed and operated successfully. The readings of temperature and humidity were able to be displayed. This result obtained and achieved objectives of this project.